A high-content library screen of putative effectors from Crohn's disease associated bacterium adherent invasive Escherichia coli LF82 - Collins, Adam (2017)
Adherent invasive E. coli (AIEC) is a recently discovered E. coli pathovar which has been closely associated with Crohn’s disease (CD). CD is a form of inflammatory bowel disease (IBD) which has seen increasing prevalence in recent years, however, its aetiology still remains elusive. The initiation of CD is thought to involve a complex interplay of factors, including: genetics, environmental factors, and the presence of key members of the gut flora, such as AIEC. While AIEC can be found in both healthy individuals and CD sufferers, the latter are believed to display a range of genetic mutations which collectively allow the entry of AIEC into host epithelial cells, and prevent bacterial removal by autophagic mechanisms. Two of the most prevalent mutations observed in CD patients include mutations in CAECAM6, a host cell receptor used by AIEC, and mutations in NOD2, an autophagy-associated protein. Once inside host cells, AIEC appears to stimulate an inflammatory response. This, along with the persistent nature of AIEC, is thought to result in chronic inflammation of the gut. Despite mounting evidence for the role of AIEC in CD, this pathovar remains understudied, with its method of invasion and effects upon host cells still poorly understood. To help characterise and determine specific genes utilised during invasion, AIEC strain LF82 was compared to other E. coli to identify coding sequences (CDSs) distinctive to LF82. From these, a library of expression vectors was created for the expression of each CDS fused to GFP. A high-content phenotypic screen (HCS) was then developed to examine the effects of LF82 CDS expression upon HeLa cells. This data was used to identify CDSs of interest, with particular focus on putative effectors. Preliminary experiments for characterisation of hits from this screen were then performed. This study resulted in the screening of hundreds of putative LF82 effectors using an HCS. This system was able to identify individual CDSs of interest, which may play a role in CD initiation and/or progression.